1982
DOI: 10.1111/j.1747-5457.1982.tb00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Facies Distribution and Petroleum Geology of the Bombay Offshore Basin, India

Abstract: In view of the recent oil and gas dicoveries in the Bombay Offshore basin, its detailed geology has been worked out in terms of its source rock and reservoir potential. An agewise, layer‐cake lithofacies analysis and five depositional model maps from Paleocene to Middle Miocene age, together with a number of paleotectonic sections has led to the reconstruction of a xeneralized depositional model of the basin as a whole. This proposed depositional model envisages the Bombay Offshore basin as a shelf‐to‐basin ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…On the contrary, the stations closer to the coast exhibit large P M s delays (0.3s–0.7s) with respect to MUL and show a thick crust (>38 km) with the thickest crust (41 km) observed at KOP, which is on the coast. Absence of surface sediments in the coastal plains, lack of evidence for the presence of Mesozoic sediments beneath the traps in the Mumbai offshore [ Basu et al , 1982] and along the DSS profiles at Koyna, together with the absence of complexities in the observed RFs indicate little possibility of thick sediments contributing to the observed delays. However, the shallow, large amplitude P to S conversions observed at several stations may possibly reflect the presence of thin layers of pre‐trap Mesozoic sediments and/or variations in the thickness of the low velocity traps.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the stations closer to the coast exhibit large P M s delays (0.3s–0.7s) with respect to MUL and show a thick crust (>38 km) with the thickest crust (41 km) observed at KOP, which is on the coast. Absence of surface sediments in the coastal plains, lack of evidence for the presence of Mesozoic sediments beneath the traps in the Mumbai offshore [ Basu et al , 1982] and along the DSS profiles at Koyna, together with the absence of complexities in the observed RFs indicate little possibility of thick sediments contributing to the observed delays. However, the shallow, large amplitude P to S conversions observed at several stations may possibly reflect the presence of thin layers of pre‐trap Mesozoic sediments and/or variations in the thickness of the low velocity traps.…”
Section: Discussionmentioning
confidence: 99%
“…The same goes for studies of the Indian shelf (e.g. Biswas 1982;Basu et al 1982), where the basalt cover is shown as continuous or only rarely penetrated by Archaean inliers. Such a continuous basalt cover would not be expected if much rifting occurred after volcanism had ceased.…”
Section: The Original Size Of the Deccanmentioning
confidence: 90%
“…The BMU is documented and regionally mapped in the Barmer, Cambay, Kutch (Chowdhary, ; Chowdhary & Singh, ; Kundal et al, ), and Bombay (Mumbai) Basins (Basu et al, ; Mehrotra et al, ; Mohan, ; Wandrey, ) as an erosional event of generally decreasing erosional depth southward (Figure , panels 5–7). In subsurface data sets, it is recognized as a regional seismically correlatable reflection event (Figure ).…”
Section: Geological Background: the Nw Indian Intraplate Basinsmentioning
confidence: 99%